A retrospective study of small-pelvis radiotherapy plus image-guided brachytherapy in stage I–II non-bulky cervical squamous cell carcinoma. (12th February 2022) - Yoshimoto, Yuya; Murata, Kazutoshi; Irie, Daisuke; Ando, Ken; Adachi, Akiko; Aoki, Hiroshi; Hirakawa, Takashi; Noda, Shin-ei; Nakano, Takashi; Ohno, Tatsuya
Abstract: We herein report a retrospective analysis of the efficacy of a combination therapy of pelvic irradiation that excluded the common iliac lymph nodes region and image-guided brachytherapy (IGBT) for non-bulky (≤4 cm) cervical cancer. Thirty-three patients with stage I–II cervical squamous cell carcinoma (≤4 cm) and without pelvic/para-aortic lymphadenopathy who were treated with definitive radiotherapy alone between February 2009 and September 2016 were included. The radiotherapy consisted of CT-based small-pelvis irradiation (whole pelvis minus common iliac lymph node area) of 20 Gy/10 fractions followed by pelvic irradiation with a midline block of 30 Gy/15 fractions and IGBT of 24 Gy/4 fractions (6 Gy/fraction for high-risk [HR] clinical target volume [CTV] D90%). In-room computed tomography (CT) imaging with applicator insertion was used for brachytherapy planning, with physical examinations and diagnostic magnetic resonance imaging (MRI) also being referred to for determination of HR CTV. Over a median follow-up of 60.5 months (range, 7–89), two patients developed distant recurrence and one developed local and distant recurrence. Two patients died from cervical cancer, one from hepatocellular carcinoma and one from non-cancerous disease. The 2/5-year local control (LC), progression-free survival (PFS) and overall survival (OS) rates were 100%/96.7%, 93.8%/90.6% and 93.9%/93.9%, respectively. No pelvic/para-aortic lymph node recurrence was observed. There were no late complications of grade 3 or higher in the small bowel, large bowel/rectum, or bladder. Our results suggest that a combination therapy of IGBT plus small-pelvis irradiation excluding common iliac lymph nodes provides reasonable clinical outcomes and can be a treatment option in non-bulky (≤4 cm) cervical squamous cell carcinoma.